Peran Kepemimpinan Transformasional Kepala Sekolah dalam Mengimplementasikan Kurikulum Merdeka - Murni, Deti; Yanto, Murni; Sahib, Abdul (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2025)
This research seeks to find out about the transformational leadership of school principals in implementing the independent curriculum in schools. This research was carried out at SMP Negeri 2 Seberang Musi Kepahiang. This research uses descriptive qualitative methods. The research object was the principal and stakeholders at SMP Negeri 2 Seberang Musi. Data collection used was through observation, interviews and documentation. The results of his research show that: a) the principal's transformational leadership is very optimal in building work enthusiasm and providing high motivation for school resources so that they are ready to implement the independent curriculum effectively, b) the implementation of the independent curriculum at SMP Negeri 2 Seberang Musi Kepahiang has developed effectively, structured and optimal, c) parents and the community work together in implementing the independent curriculum in schools. The research results can be applied to educational institutions that are characterized as Institutions with a Commitment to Educational Transformation